2011
DOI: 10.1093/jxb/err135
|View full text |Cite
|
Sign up to set email alerts
|

Root apoplastic barriers block Na+ transport to shoots in rice (Oryza sativa L.)

Abstract: Rice is an important crop that is very sensitive to salinity. However, some varieties differ greatly in this feature, making investigations of salinity tolerance mechanisms possible. The cultivar Pokkali is salinity tolerant and is known to have more extensive hydrophobic barriers in its roots than does IR20, a more sensitive cultivar. These barriers located in the root endodermis and exodermis prevent the direct entry of external fluid into the stele. However, it is known that in the case of rice, these barri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
152
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 194 publications
(172 citation statements)
references
References 58 publications
14
152
0
2
Order By: Relevance
“…Here, findings of less Na C accumulation in shoots in the tolerant rice varieties/ transgenic lines are similar with finding of Krishnamurthy et al 17 who reported that additional suberized hydrophobic barriers and reduced entry of Na C into shoots under salt stress conditions. Therefore, our findings in sustaining least Na C in shoot suggest that PDH45 gene may be involved similar salinity tolerance mechanism in defined tobacco (dicot) and rice (monocot) transgenic plants in response to salinity stress.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Here, findings of less Na C accumulation in shoots in the tolerant rice varieties/ transgenic lines are similar with finding of Krishnamurthy et al 17 who reported that additional suberized hydrophobic barriers and reduced entry of Na C into shoots under salt stress conditions. Therefore, our findings in sustaining least Na C in shoot suggest that PDH45 gene may be involved similar salinity tolerance mechanism in defined tobacco (dicot) and rice (monocot) transgenic plants in response to salinity stress.…”
Section: Discussionsupporting
confidence: 91%
“…16 The salinity tolerant variety (Pokkali) revealed more extensive hydrophobic barriers in its roots as compared to the salinity susceptible variety (IR20). 17,20 The PDH45 overexpression enhances salinity tolerance without compromising yield as compared to WT (IR64). 11 The results of this study, revealed differential accumulation of Na C in salinity stress in 3 rice varieties and 2 transgenic lines analyzed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Severe reductions in extracellular water potentials due to high salt loads can produce rapid dehydration and consequent damage of cells, and the similarities between salt and drought stresses are remarkable (Munns 2002). In the case of rice, most, if not all, salt-induced damage in the leaves might be due to osmotic stresses caused by Na + buildup in the leaf apoplast (the "Oertli hypothesis"; Flowers et al 1991;Krishnamurthy et al 2011). Less clear, however, are the mechanisms underlying the secondary, "ion-specific" aspects of salt stress (Munns et al 1995).…”
Section: Osmotic and Ionic Effects: What Is The Difference?mentioning
confidence: 99%
“…As seen under salt-stress, the development of apoplastic barriers (such as the endodermis) has been correlated with increasing resistance to the radial flow of water and solutes in roots, resulting in reduced ion uptakes (i.e. Na + ) into the shoots and in better survival under subsequent acute stress (Krishnamurthy et al, 2011).…”
Section: Antioxidant Enzyme Activitiesmentioning
confidence: 99%